Evaluation of tissue in repair with natural latex and / or hyaluronic acid in surgical bone defects - Issa,João Paulo Mardegan (2021)
Abstract This study evaluated the bone repair in surgical defects of rats treated with hyaluronic acid (HA) associated or not with Hevea brasiliensis fraction protein (F-1). Bone defect were created in 15 albino Wistar rats divided into 3 groups (n=5): Control group (1) - blood clot; HA group (2) - 0.5% hyaluronic acid; HAF1 group (3) - 0.1% F-1 protein fraction dissolved in 0.5% hyaluronic acid. After 4 weeks, the animals were euthanized and the bone repair was evaluated through histomorphometric analysis, zymography and immunohistochemistry. The neoformed bone area did not show a significant difference (p = 0.757), but there was a tendency for bone trabeculation to increase in the groups HA and HAF1. For immunohistochemically analysis, there was a difference in vascular endothelial growth factor (VEGF) labeling (p = 0.023), being higher in the groups HA and HAF1 than the control group. No significant difference in bone sialoprotein (BSP) (p = 0.681), osteocalcin (p = 0.954), however, significant difference in platelet endothelial cell adhesion molecule-1 (CD-31) (p = 0.040), with HAF1 group being significantly lower than the control. For zymographic analysis, there was no significant difference for metalloproteinase-2 (MMP-2) (p = 0.068), but there was a tendency to increase MMP-2 in the HA group. Despite the influence on angiogenic factors and the apparent tendency for greater trabeculation in the HA and HAF1 groups, there was no significant difference in the area of ​​newly formed bone tissue in the analyzed period.